Sarcoidosis of the pleura – A case report - Jovanović, Dragana; Vučinić, Violeta; Stević, Ruža; Roksandić-Milenković, Marina; Samardžić, Natalija; Velinović, Marta; Stjepanović, Mihailo (Vojnosanitetski pregled, 2014)
Introduction. Pleural involvement is an uncommon manifestation of sarcoidosis. It may manifest as pleural effusion, pneumothorax, pleural thickening and nodules, hydropneumothorax, trapped lung, hemothorax, or chylothorax. The incidence of pleural effusion with sarcoidosis ranges from 0% to 5% but has been reported to be as high as 7.5%. Pleural effusions complicate sarcoidosis in < 3% of patients. Case report. We reported a 64-year-old male patient with chronic multiorgan sarcoidosis. This patient developed pleural sarcoidosis with massive pleural effusion several years after the diagnosis of sarcoidosis. A definitive diagnosis of a sarcoid pleural effusion was based on a biopsy demonstrating noncaseating granuloma. The patient responded well to the treatment (methotrexate and methylprednisolone) with a complete withdrawal of pleural effusion following five weeks of the treatment beginning. Conclusion. The presented patient is a rare case of pleural involvement of sarcoidosis with massive effusion, who responded well to the treatment.